Nelayan e-profiling for Kota Samarahan - Khairul Azib, Masri (Universiti Malaysia Sarawak (UNIMAS), 2020)
The absent of hub or platform for fisherman to keep track of their activities will lead less productivity. For the time being fishermen catch and sold their fish without keeping track their activities. This project is aiming to develop a web-based profiling system for fishermen at Kota Samarahan to a systematic approach to help secure their data more effectively. This project also can help collect fisherman data easily and centralized the data. With centralized the data, important data and fishermen profile won’t be lost and avoid data confusion. Furthermore, fishermen at Kota Samarahan can keep track their activities using this web-based system eprofiling by all recorded fish caught.